2021
DOI: 10.1111/jgh.15357
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activity assessment by 18F‐fluorodeoxyglucose positron emission tomography in patients with hepatocellular carcinoma undergoing Yttrium‐90 transarterial radioembolization

Abstract: Background and Aim 18F‐fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) is a functional image technique that can inform clinical decisions related to prognosis. We investigated the predictive role of 18F‐fluorodeoxyglucose PET/CT in patients with hepatocellular carcinoma (HCC) undergoing Yttrium‐90 (Y‐90) transarterial radioembolization (TARE). Methods Patients with HCC treated with TARE and pre‐TARE PET/CT scan were recruited between 2009 and 2013. Maximum standardized uptake value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In contrast, Kucuk et al 14 showed that higher SUV max HCC is associated with better progression-free survival rates in patients with unresectable HCC. In a study by Kim et al 17 involving 40 patients with HCC, TLR (>2.1) on 18 F-FDG PET/CTwas not predictive of treatment response, progression, or death. The controversial results could be attributed to the small number of enrolled patients and heterogeneous clinical conditions among the studies.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In contrast, Kucuk et al 14 showed that higher SUV max HCC is associated with better progression-free survival rates in patients with unresectable HCC. In a study by Kim et al 17 involving 40 patients with HCC, TLR (>2.1) on 18 F-FDG PET/CTwas not predictive of treatment response, progression, or death. The controversial results could be attributed to the small number of enrolled patients and heterogeneous clinical conditions among the studies.…”
Section: Discussionmentioning
confidence: 86%
“…A few studies have evaluated the values of TLR or SUV on 18 F-FDG PET/CT to predict the prognosis of patients with HCC treated with 90 Y TARE. [13][14][15][16][17] Conflicting results, however, were obtained with regard to the value of 18 F-FDG uptake after 90 Y TARE. Abuodeh et al 13 and Jreige et al 15 demonstrated that patients with HCC with 18 F-FDG avidity, high SUV max , or high TLR have a worse prognosis.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations